1997
DOI: 10.1182/blood.v89.5.1800
|View full text |Cite
|
Sign up to set email alerts
|

Severe Combined Immunodeficiency Mice Engrafted With Human T Cells, B Cells, and Myeloid Cells After Transplantation With Human Fetal Bone Marrow or Liver Cells and Implanted With Human Fetal Thymus: A Model for Studying Human Gene Therapy

Abstract: To develop an in vivo model wherein human hematopoiesis occurs, we transplanted severe combined immunodeficiency (SCID) mice with either human fetal bone marrow (HFBM) or human fetal liver (HFL). After transplantation of SCID mice with cultured HFBM (BM-SCID-hu mice) or HFL cells (Liv-SCID-hu mice), significant engraftment of the mouse bone marrow (BM) and population of the peripheral blood with human leukocytes was detected. Human colony-forming unit–granulocyte macrophage and burst forming unit-erythroid wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0

Year Published

1997
1997
2004
2004

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 40 publications
1
7
0
Order By: Relevance
“…Our rationale for using the NOD‐SCID strain was based on accumulating evidence that NOD‐SCID mice are the most sensitive recipients for transplantable human cells with multiple potentials (Cashman et al , 1997; Pflumio et al , 1996) and are particularly suitable for human B‐lymphoid differentiation (Hogan et al , 1997; Pflumio et al , 1996), and may also support T‐cell differentiation in vivo (van der Loo et al , 1998; Yurasov et al , 1997). Furthermore, the successful development of T cells from fetal liver and cord blood progenitors in murine FTOC has been demonstrated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our rationale for using the NOD‐SCID strain was based on accumulating evidence that NOD‐SCID mice are the most sensitive recipients for transplantable human cells with multiple potentials (Cashman et al , 1997; Pflumio et al , 1996) and are particularly suitable for human B‐lymphoid differentiation (Hogan et al , 1997; Pflumio et al , 1996), and may also support T‐cell differentiation in vivo (van der Loo et al , 1998; Yurasov et al , 1997). Furthermore, the successful development of T cells from fetal liver and cord blood progenitors in murine FTOC has been demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…In murine thymus, however, cell proliferation was lower than in human FTOC, and the production of single‐positive CD8 + cells was compromised because murine class I molecules are poor effectors of the CD8 selection. Nevertheless, these studies demonstrated that human T‐lymphoid differentiation could proceed in a murine thymic environment in vitro and recent data suggest that this might occur also in vivo in NOD‐SCID recipients (van der Loo et al , 1998; Yurasov et al , 1997). Since active human B lymphopoiesis and myelopoiesis take place in vivo in NOD‐SCID mice (Cashman et al , 1997; Kollmann et al , 1994; Pflumio et al , 1996; Vormoor et al , 1994), and in vitro in the presence of murine stromal feeders (Berardi et al , 1997; Galy et al , 1995a; Rawlings et al , 1997), one can conclude that a murine environment can support the differentiation of primitive human haemopoietic cells in all lymphoid and myeloid pathways at least when cells from a fetal source are used.…”
mentioning
confidence: 99%
“…Low levels of human cells were detectable in the marrow or peripheral tissues of the scid mouse hosts [25]. Investigators have used SCID-hu mice as model systems for the study of human stem cell phenotype and differentiation [42][43][44][45][46][47][48][49][50][51][52], human gene therapy protocols [53][54][55], human T-cell differentiation [56], and homing of human myeloma cells to the bone marrow [57]. SCID-hu mice, in combination with cotransplanted thymic fragments, have been used to investigate the primitive hemopoietic stem cell that populates the T-cell lineage [42,58], for studies of human T-cell function [59,60], and for infection of human T cells and thymus with HIV [61,62].…”
Section: Scid-hu Micementioning
confidence: 99%
“…Other studies using in vivo models include the SCID‐hu model, in which human CD34 + cells are coimplanted with T cell–depleted human fetal thymus [16]. Hence, both FTOC and SCID‐hu models are based on the availability of a fetal thymic tissue.…”
Section: Introductionmentioning
confidence: 99%